(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
To treat the hard soil of the furrow surface formed after watering the plants, a battery of plate knives is installed on the ridge: central, right and left. The working section is lowered onto the soil so that the central plate knife of the battery is located on the longitudinal axis of the furrow.